Conservation Agriculture: Global Prospects and Challenges 2013
DOI: 10.1079/9781780642598.0263
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture in Eastern and Southern Africa.

Abstract: This chapter describes the history and current status of conservation agriculture (CA) in East and South Africa. It examines research results from East and South Africa in an effort to develop a clearer picture of the future of CA systems in the region. The yield and economic benefits, as well as the importance of mulch and crop rotation are described. The effect of CA on (i) soil quality (physical, chemical and biological), (ii) soil water balance, and (iii) weeds, pests and diseases is presented. Several cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…This has led to CA receiving support in national agriculture and rural development policy and projects (e.g. Arslan et al, 2014;Whitfield et al, 2015), and to become a focus for private and third sector interventions (Godfray et al, 2010;Lipper et al, 2014;Pretty and Brahuchra, 2014;Wall et al, 2014). Despite enthusiasm for CA across levels, uncertainty around performance and trade-offs associated with CA practice and its compatibility with diverse livelihood strategies and varied agro-ecological conditions have caused some to question its universal efficacy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to CA receiving support in national agriculture and rural development policy and projects (e.g. Arslan et al, 2014;Whitfield et al, 2015), and to become a focus for private and third sector interventions (Godfray et al, 2010;Lipper et al, 2014;Pretty and Brahuchra, 2014;Wall et al, 2014). Despite enthusiasm for CA across levels, uncertainty around performance and trade-offs associated with CA practice and its compatibility with diverse livelihood strategies and varied agro-ecological conditions have caused some to question its universal efficacy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that CA promotion has been led by development experts and researchers, particularly in the eastern and southern Africa where the approach was introduced without adapting the practices (e.g. commonly referred to as "top-down" development approach) (Wall et al, 2013).…”
Section: Whose Perspective Is Vocal On Ca?mentioning
confidence: 99%
“…Not only has CA been reported to improve the soil aspect and yields but also profitability and income (Wall et al, 2013;Asfaw et al, 2014;Thierfelder et al, 2015a;Mupangwa et al, 2016;Thierfelder et al, 2016). Comparing CA maize systems with conventional tillage systems, studies conducted across the country reported that the former has less labour costs, has higher gross margins and lowers risk of crop failure (Ngwira et al, 2011;Ngwira et al 2012a;Ngwira et al, 2013;Wall et al, 2013;Ngwira et al, 2014a;Thierfelder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations